2002
DOI: 10.1152/japplphysiol.00019.2001
|View full text |Cite
|
Sign up to set email alerts
|

Interactive effects of mental and physical stress on cardiovascular control

Abstract: Physiological responses to mental tasks and physical exercise were studied independently and combined. We hypothesized that combined mental and physical stresses produce a synergistic interaction. We studied cardiovascular responses to 5 min of static handgrip, mental arithmetic, and the combined stimuli in random order in 12 healthy subjects. Muscle sympathetic nerve activity (SNA) and mean arterial blood pressure (MAP) responses to handgrip and the combined stimuli exceeded responses to mental arithmetic, ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
40
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(51 citation statements)
references
References 35 publications
10
40
1
Order By: Relevance
“…16,54 In our study it was shown that the effect of this test on parameters of central AS was similar but less pronounced compared to that of the FHG. Our data are in agreement with the results of a previous study, which showed that acute mental test had an unfavourable effect on AS and wave reflection that lasted for a prolonged period.…”
Section: Lydakis Et Alsupporting
confidence: 49%
See 1 more Smart Citation
“…16,54 In our study it was shown that the effect of this test on parameters of central AS was similar but less pronounced compared to that of the FHG. Our data are in agreement with the results of a previous study, which showed that acute mental test had an unfavourable effect on AS and wave reflection that lasted for a prolonged period.…”
Section: Lydakis Et Alsupporting
confidence: 49%
“…A recent study showed a prolonged unfavourable effect of mental stress on indices of aortic stiffness and wave reflection. 15 Activation of the sympathetic nervous system has been documented during both mental stress 16 and exercise (static 17 or dynamic 18 ).…”
Section: Introductionmentioning
confidence: 99%
“…[9] Cardiovascular system reacts to this stress as a result of increased output and decreased reuptake of catecholamines by sympathetic part of autonomic nervous system. [2] This is supplemented by the fact that during menstruating phase, the level of estrogen hormone falls and levels of folliclestimulating hormone (FSH) and luteinizing hormone (LH) rise. As a result, there is increased sympathetic and low parasympathetic activity on exposure to stressors.…”
Section: Discussionmentioning
confidence: 99%
“…[2,3] All subjects were explained in detail in the language understood by them and to their satisfaction about the procedure of the tests to be conducted on them. Voluntary written informed consent was taken from all the subjects.…”
Section: Study Populationmentioning
confidence: 99%
See 1 more Smart Citation